2017
DOI: 10.1002/2211-5463.12284
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products reduce the calcium transient in cardiomyocytes by increasing production of reactive oxygen species and nitric oxide

Abstract: Advanced glycation end products (AGE) are central to the development of cardiovascular complications associated with diabetes mellitus. AGE may alter cellular function through cross‐linking of cellular proteins or by activating the AGE receptor (RAGE). However, the signalling molecules involved during AGE stimulation in cardiomyocytes remain unclear. Here, we investigated the effects of AGE treatment on intracellular calcium homeostasis of isolated cardiomyocytes and studied the activation of signalling molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…A similar mechanism could explain why the restoration of prolonged APD by AG was mimicked by knockdown of the RAGE gene in HG-cultured cell model. On the other hand, RAGE activation has been shown to enhance nitric oxide production and cell damage by up-regulation of inducible nitric oxide synthase (Sumi and Ignarro, 2004;Hegab et al, 2017). However, a previous study showed no increase in nitric oxide production in STZ-induced diabetic rat hearts (Stadler et al, 2005), implicating that the protective effect of AG in the diabetic heart may not necessarily due to inducible nitric oxide synthase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism could explain why the restoration of prolonged APD by AG was mimicked by knockdown of the RAGE gene in HG-cultured cell model. On the other hand, RAGE activation has been shown to enhance nitric oxide production and cell damage by up-regulation of inducible nitric oxide synthase (Sumi and Ignarro, 2004;Hegab et al, 2017). However, a previous study showed no increase in nitric oxide production in STZ-induced diabetic rat hearts (Stadler et al, 2005), implicating that the protective effect of AG in the diabetic heart may not necessarily due to inducible nitric oxide synthase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a key factor in the pathophysiology of diet-related cardiovascular complications [ 36 , 37 ]. Very recently, RAGE activation, following binding with AGEs, has been shown to mediate oxidative stress in cardiomyocytes [ 38 ]. Here we confirmed that mice exposed to fructose, in both the liquid and solid formulations, exhibited a massive increase in myocardial oxidative stress, as suggested by markers of peroxidation of cell membrane lipids and radical-induced DNA damage as well as activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of CD38 expression also signals maturation of dendritic cells during inflammatory cytokine activation and acts as a modulating adhesion and signaling molecule between dendritic cells and lymphocytes (105). In cardiomyocytes, exogenous stimulants may stimulate an increase in intracellular calcium, which leads to activation of CD38 (147). CD38 expression has also been shown to increase with age (65), and this is most likely attributed to an age-related increase in circulating inflammatory cytokines, and reduced CD38 function has been associated with poor immune responses.…”
Section: B Cd38/cd39/cd73/cd157 and Secondary Messenger Signalingmentioning
confidence: 99%